The Effect of Good Corporate Governance Towards Idiosyncratic Risk - Cintya Yuliana Limantara; Werner R. Murhadi; Liliana Inggrit Wijaya (Journal of Management and Business, 2020)
This study aims to analyze the effect of good corporate governance towards idiosyncratic risk as a proxy with corporate governance variable as board size, independent director, women, firm size, firm performance, and firm age. The object of this study uses companies listed in the Indonesia Stock Exchange and Philippine Stock Exchange using agency theory. This study uses quantitative approach and multiple linear regression to analyze the data. The target populations of this study are manufacturing companies that listed in Indonesia Stock Exchange and Philippine Stock Exchange in 2014-2018 which are equal to 615 and 200 year observations. The results in Indonesia showed that board size, women, and firm age had negatif effect on idiosyncratic risk. On the other hand, firm size do not show the effect on idiosyncratic risk and firm performance had positive effect on idiosyncratic risk. However, the results in Philippine showed that board size had positive effect on idiosyncratic risk. While, women and firm size do not show the effect on idiosyncratic risk but firm performance and firm age had negatif effect on idiosyncratic risk.